Assessment of the dynamics of individualized internal exposure dose irradiation of PSRER workers of the Polesie State Radiation-Ecological Reserve - Demenkovets, Nikolai; Shabaleva, Maryna; Nenashev, Roman (Journal of the Belarusian State University. Ecology, 2025)
The purpose of the study was to analyze the long-term dynamics of the internal radiation dose of PSRER employees, as well as to determine the factors that determine the variation of its indicators in different categories of the examined personnel. A statistical analysis of the internal radiation dose of the reserve employees for the period from 2007 to 2021 was carried out. The results of 9525 measurements obtained from monitoring the internal radiation dose of personnel on a spectrometer (counter) of human radiation SKG-AT 1316 were studied. Long-term, gender, professional, age and local differences in the obtained data were determined. It was revealed that the level of internal radiation dose of personnel in most cases (4317 measurements) does not exceed 0.01 mSv/year, and in 87 % of measurements it does not exceed 0.055 mSv/year; only 1.3 % of employees had internal radiation dose indicators higher than 2 mSv/year. Over the long-term observation period, the highest values were observed in 2010 and 2011 – 0.029 and 0.027 mSv/year, respectively. Analysis of the internal radiation dose in representatives of different specialties allowed us to determine the highest median dose levels in gamekeepers (0.02 mSv/year), horse breeders, firefighters and drivers, and the lowest in engineering and research personnel. Based on the measurements, the reserve personnel can be divided into 3 professional groups. According to the data obtained, the level of internal radiation dose was statistically significantly (p < 0.05) higher in men than in women (2 times). Among workers from various populated areas, the highest values were noted among residents of the city of Narovlya (0,3 mSv/year). Relatively high levels of internal radiation dose were determined for employees from the villages of Berezovka and Malishev (0.1 mSv/year). When analyzing the age dependencies of the formation of the internal radiation dose, 5 age groups were identified, which were distinguished by statistically significant differences in this indicator: the maximum levels were found in individuals aged 35–46 years (0.015 mSv/year), and the minimum levels were found in individuals aged 18–26 years (0.007 mSv/year).
Keywords: radioactive contamination; internal dose; PSRER; WBC measurements